Exploration of Optical Fiber and Laser Cutting Head Applications in High-Radiation Environments for Fast Reactor Spent Fuel Reprocessing - Qi Chen; Jiarong Zheng; Jia Zhou; Zhengbin Chen; Zengliang Mo; Zhi Cao; Chunwei Tang; Tianchi Li; Fang Liu; Taihong Yan; Weifang Zheng (Sensors)
Fast-neutron reactors are an important representative of Generation IV nuclear reactors, and due to the unique structure and material properties of fast reactor fuel, traditional mechanical cutting methods are not applicable. In contrast, laser cutting has emerged as an ideal alternative. However, ensuring the stability of optical fibers and laser cutting heads under high radiation doses, as well as maintaining cutting quality after irradiation, remains a significant technical challenge. Here, we study the performance changes in optical fibers exposed to a total radiation dose of 105 Gy, focusing on power transmission and thermal characteristics. By integrating irradiated optical fibers with irradiated laser cutting heads, simulated cutting experiments on the hexagonal tubes of spent fuel from fast reactors (fast reactor simulation assembly) were conducted. Critical cutting quality parameters, including kerf width, surface roughness, and slagging length, were analyzed. The results indicate that, while the power transmission performance of irradiated optical fibers shows slight degradation, its impact on cutting quality is minimal. High-quality cutting can still be achieved under optimized parameters. This study confirms the feasibility of laser cutting technology in high-radiation environments and provides essential technical support for its application in nuclear fuel reprocessing.